Transmission expansion planning via power flow controlling technologies - Franken, Marco; Barrios, Hans; Schrief, Alexander B; Moser, Albert (IET generation, transmission & distribution, 2020)
The transition from conventional towards renewable energy systems requires additional transmission capacities and higher operational flexibility to overcome contingency situations. This study presents a novel transmission expansion planning approach for the simultaneous placement of AC systems and power flow controlling technologies including high voltage direct current, phase shifting transformers (PSTs) and thyristor controlled series compensators (TCSCs). The approach is formulated as a mixed-integer linear programming optimisation problem and the operating point of power flow controlling devices is endogenously determined by minimising expansion costs. Both PSTs and TCSCs are integrated into the optimisation problem by means of new mathematical formulations. PSTs are presented in more detail considering the PST impedance, which is modelled as an equivalent phase shift. The controllable series impedance of TCSCs is also represented as an equivalent phase shift. Exemplary results based on a synthetic 120 bus system show a significant potential of PSTs and TCSCs to reduce expansion costs as well as to lower the requirement for new transmission capacities. The simultaneous employment of these technologies reduces the expansion costs within the test system between 18.7 and 32.4% compared to those costs generated by the sole reinforcement by AC systems.